UMP develops human capital for industry in Pahang - Yong, Ying Mei (UMPSA, 2023)
KUANTAN, 7 March 2023 - Confucius Institute (CI), Universiti Malaysia Pahang organised the Mandarin Technical Course Certificate Presentation Ceremony at the steel making plant, Alliance Steel (M) Sdn. Bhd. (ASSB) located in Malaysia-China Kuantan Industrial Park (MCKIP).